A Scalable Energy–Economy Model for State-Level Policy Analysis Applied to a Demand-Side Management Program. Issue 4 (November 2020) - Wendling, Zachary A.; Warren, David C.; Rubin, Barry M.; Carley, Sanya; Richards, Kenneth R.
Over the past two decades, states and cities implemented low-carbon energy development, renewable portfolio standards, demand-side management (DSM), renewable energy production incentives, green building requirements, regional carbon trading agreements, and other energy-based economic development initiatives. Yet the dearth of state-level and substate-level models makes it difficult to predict the effects of such actions. This article addresses this shortcoming by presenting the performance results of the new Indiana Scalable Economy and Energy Model (IN-SEEM)—a model utilizing a dynamic, simultaneous equations framework—and demonstrates the model's capabilities with an analysis of electricity price increases from a DSM program in the state of Indiana. Overall performance of the model is strong, with high adjusted R 2 values and low mean absolute percent errors for most of 30 endogenous variables. A DSM price increase analysis finds variation in impact across the state's 10 major economic sectors and small changes in energy consumption.